1994
DOI: 10.1038/ki.1994.300
|View full text |Cite
|
Sign up to set email alerts
|

A randomized multicenter clinical trial comparing isosmolar Icodextrin with hyperosmolar glucose solutions in CAPD

Abstract: The osmotic effectiveness of a large molecular weight glucose polymer fraction (Icodextrin) as a novel "colloid" osmotic agent in peritoneal dialysis was established, but the long-term safety remained undetermined. A randomized, controlled multicenter investigation of Icodextrin in ambulatory peritoneal dialysis (MIDAS) was undertaken to evaluate the long-term safety and efficacy by comparing daily overnight (8 to 12 hr dwell) use of isosmolar Icodextrin (282 mOsm/kg) with conventional 1.36% (346 mOsm/kg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
240
5
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(276 citation statements)
references
References 23 publications
14
240
5
13
Order By: Relevance
“…Icodextrin addresses one of the critical areas of vulnerability in fluid management in patients on PD: maintaining adequate UF during the long dwell. Studies that examined the relationship between patient transport status and net UF (22,23,25,27) showed that the improvements in net UF with icodextrin were greatest in patients with high and high-average membrane transport characteristics. Consistent with that observation, evidence derived from our review showed better UF in patients receiving icodextrin with high, high-average, and low-average but not low transport characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Icodextrin addresses one of the critical areas of vulnerability in fluid management in patients on PD: maintaining adequate UF during the long dwell. Studies that examined the relationship between patient transport status and net UF (22,23,25,27) showed that the improvements in net UF with icodextrin were greatest in patients with high and high-average membrane transport characteristics. Consistent with that observation, evidence derived from our review showed better UF in patients receiving icodextrin with high, high-average, and low-average but not low transport characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The full-text versions of 34 studies were retrieved, 22 of which were subsequently excluded. Among other studies, 3 articles (18)(19)(20) came from the same study at different stages and another 2 articles (21,22) from 1 study were published in different journals. Finally, 9 trials published in 12 articles (18-29) with a total of 1190 participants were included in this present review, yielding 633 subjects in the icodextrin group and 557 subjects in the glucose group.…”
Section: Trial Flow and Study Characteristicsmentioning
confidence: 99%
“…Ultrafiltration with icodextrin is attributable to sustained oncotic pressure differences exerted primarily between albumin in plasma and glucose polymers in dialysate, as has been well established (1,26,29). Based on a detailed analysis of UF in APD patients (11), Venturoli et al (21) recently suggested that plasma oncotic pressure was the primary factor governing the variability of UF-versus-time curves with icodextrin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there has been growing concern that the hyperosmolality and low pH of these solutions may damage the peritoneum and thereby threaten its viability as a dialyzing membrane. [26] When the residual renal function declines, there may be a need for an increase in the number of the hypertonic glucose exchanges. [27] The use of peritoneal dialysis solutions not using glucose as their osmotic agent has been suggested as a strategy to reduce glucose exposure in peritoneal dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Standard solutions contain different concentrations of glucose as their osmotic agents. Although these solutions have various advantages, the metabolic side effects such as hyperglycemia and hyperinsulinemia as well as a deficiency of ultrafiltration due to the rapid absorption of glucose through peritoneal membranes [14] brought newly developed peritoneal solutions into consideration.…”
Section: Introductionmentioning
confidence: 99%